2017
DOI: 10.1103/physrevb.96.245424
|View full text |Cite
|
Sign up to set email alerts
|

Modification of electronic structure, magnetic structure, and topological phase of bismuthene by point defects

Abstract: This paper reveals how the electronic structure, magnetic structure, and topological phase of two-dimensional (2D), single-layer structures of bismuth are modified by point defects. We first showed that a free-standing, single-layer, hexagonal structure of bismuth, named h-bismuthene, exhibits nontrivial band topology. We then investigated interactions between single foreign adatoms and bismuthene structures, which comprise stability, bonding, electronic structure, and magnetic structures. Localized states in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Nitrogene, 44 phosphorene, 34 arsenene, 45 antimonene, 46 and bismuthene 48 have recently gained importance due to their semiconducting properties. Furthermore, due to the large spin-orbit coupling effects shown by antimonene, bismuthene, and their compounds, 48,[131][132][133] these layered structures have attracted special interest owing to their possible topologically non-trivial states in specific conditions. Apparently, as the row number increases, the topological insulator properties stand out gradually.…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogene, 44 phosphorene, 34 arsenene, 45 antimonene, 46 and bismuthene 48 have recently gained importance due to their semiconducting properties. Furthermore, due to the large spin-orbit coupling effects shown by antimonene, bismuthene, and their compounds, 48,[131][132][133] these layered structures have attracted special interest owing to their possible topologically non-trivial states in specific conditions. Apparently, as the row number increases, the topological insulator properties stand out gradually.…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%
“…[184][185][186][187][188][189][190][191] Also, hb-Bi placed on the Si(0001) substrate was shown to possess a topologically non-trivial phase. 192 Kadioglu et al 132 found that while the pristine hb-Bi monolayer displays topologically non-trivial behavior, aw-Bi does not. Not only pristine and bare Bi ultrathin films and monolayers, but also the topological behaviors of defected Bi structures have been subject of studies.…”
Section: E Bismuthenementioning
confidence: 99%
See 1 more Smart Citation
“…36 Monolayer hb-bismuthene is topologically non-trivial based on the density functional theory (DFT)-spin-orbit coupling (SOC) calculations. 37 Also, hb-Bi placed on a Si substrate was shown to be topologically non-trivial. DFT-SOC calculations of aw-Bi indicated a trivial topological order.…”
Section: Introductionmentioning
confidence: 99%
“…DFT-SOC calculations of aw-Bi indicated a trivial topological order. 37 (v) Finally, significant progress has been made towards the synthesis of SL antimonene and bismuthene structures. Ultrathin films of antimonene have been synthesized using methods such as mechanical/liquid-phase exfoliation or epitaxial growth.…”
Section: Introductionmentioning
confidence: 99%